Flail arms in a parachutist: an unusual presentation of hereditary neuropathy with liability to pressure palsies. Issue 6 (1st December 2002) - Marriott, M; Macdonell, R; McCrory, P
Abstract : Parachuting is a popular sport but carries with it an appreciable injury risk. The case is presented of severe arm weakness after a parachute jump in a susceptible young woman.